Quality of life and financial implications of depression in India - Neha Purohit; Aarti Goyal; Shubh M. Singh; Sandeep Grover; Shankar Prinja (Indian Journal of Psychiatry)
Background: Depression is a major public health problem in India, placing a substantial burden on individuals, families, and society. Besides clinical assessment, quality of life (QoL) and out-of-pocket expenditure (OOPE) are key measures to assess the impact of this condition on a patient’s wellbeing. However, there is a dearth of published evidence on both these outcomes from India. Moreover, there is no evidence of concordance between common tools for measuring QoL in patients with depression in Indian settings. Aim: This study aims to assess QoL using the EQ-5D-5L and WHOQOL-BREF tools, estimate OOPE for depression care, identify factors associated with QoL and OOPE, and explore the correlation between the QoL derived from both tools. Methods: A cross-sectional survey was conducted at a public tertiary care facility in India, involving semistructured interviews with 259 depression patients. Mean QoL and OOPE were estimated. Multiple linear regression was employed to identify factors associated with QoL and OOPE, while Pearson’s correlation coefficient was used to assess the relationship between EQ-5D-5L and WHOQOL-BREF domain scores. Results: The mean EQ-5D-5L utility score was 0.731, while the QoL derived from WHOQOL-BREF ranged from 50.41 to 61.00, across the four domains. Factors like depression severity, perceived support, physical activity, and literacy were significantly associated with QoL. The annual OOPE for depression treatment was ₹35,101. Moderate to strong correlations were observed between EQ-5D-5L and WHOQOL-BREF “physical health” (r = 0.605) and “psychological” (r = 0.553) domains, with weaker correlations for “social relationships” (r = 0.255) and “environment” (r = 0.292). Conclusion: Depression leads to significant financial burden on the patient and the family and is associated with lower QoL. Future research should explore the addition of relevant bolt-on dimensions to the EQ-5D-5L to improve its sensitivity in depression assessment.